Telekom Malaysia Berhad / Nur Badrina Munirah Mohamed - Mohamed, Nur Badrina Munirah (Faculty of Business and Management, 2023)
For completing my degree journey, I am undergoing my industrial training at Telekom Malaysia Berhad for 6 months. This course is mandatory for all final year students, and it was an opportunity for undergraduate students to learn and experience real working life. Industrial training or called internship also helps me by encouraging career development, enhance skills and getting knowledge about working life. I am thankful and honored being accepted by Telekom Malaysia to undergoing my internship under Service Culture department. In this report, I included my internship journey in the company that is valuable for myself and helps me improve leadership, communication and interpersonal skills. The purpose of writing this report is to evaluate what I have learned from my internship program, what I observed in the company and what value I have gained from this training. Under this report, I am including the company’s background and I believed it is important to know the organization we entered. Training reflection also included summarizing my job scope, activities, and task I have done and my department organization. For analyzing Telekom Malaysia, I have prepared my SWOT analysis and identifying their strengths, weaknesses, opportunities and threats as well. Moreover, I also stated the recommendations that can help in improving and elevating Telekom Malaysia’s management, sales and production.